Analisis sistem informasi akuntansi dalam menunjang pengelolaan persediaan obat pada rumah sakit umum pusat Prof. Dr. R. D. Kandou - Wuwungan, Christian Elkana; Gamaliel, Hendrik; Sardjono, Olivia Y. M. (Riset Akuntansi dan Portofolio Investasi, 2025)
This study examines how the accounting information system (AIS) supports drug inventory management at Prof. Dr. R. D. Kandou General Hospital, a type-A referral hospital in North Sulawesi. Effective inventory management is essential to ensure the timely availability of medications and minimize stockouts in clinical services. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation from the pharmacy unit, procurement division, and finance department. The findings show that the AIS—integrated through SIMAN and SAKTI—facilitates procurement, recording, stock monitoring, and reporting processes. The system improves accuracy in tracking inventory movements and supports managerial decision-making. However, challenges remain, particularly the limited integration between units and the continued reliance on manual documentation before digital input, which reduces efficiency and increases the risk of errors. Strengthening system integration and enhancing user training are required to optimize the AIS’s role in supporting inventory control and operational efficiency.